2022
DOI: 10.1227/neu.0000000000002252
|View full text |Cite
|
Sign up to set email alerts
|

Increased Circulating Chemokines and Macrophage Recruitment in Growing Vestibular Schwannomas

Abstract: BACKGROUND:There is evidence that macrophage infiltration in the tumor microenvironment promotes vestibular schwannoma (VS) growth. Efficacy of bevacizumab in NF2-associated VS demonstrates the value of therapies targeting the microvascular tumor microenvironment, and tumor-associated macrophages (TAMs) may represent another druggable target.OBJECTIVE:To characterize the relationship between growth, TAM infiltration, and circulating monocyte chemokines in a large cohort of patients with VS.METHODS:Immunostaini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…The inflammatory mediators secreted from the TME likely drives recruitment of monocytes into the tumour and support the TAM-rich identity of VS. Indeed, previous immune profiling studies in VS have shown that schwannoma cells and TAMs secrete inflammatory factors, such as interleukin (IL)-2, IL-6 and CCL20, and that increased levels of circulating monocytic chemokines are observed in plasma samples from growing VS cases 45,46 . Supporting this, we have shown that classically-activated TAMs and transitioning monocytes have extensive interaction networks in Antoni A regions, namely with other myeloid cells, vasculature and some Schwann cell populations.…”
Section: Discussionmentioning
confidence: 99%
“…The inflammatory mediators secreted from the TME likely drives recruitment of monocytes into the tumour and support the TAM-rich identity of VS. Indeed, previous immune profiling studies in VS have shown that schwannoma cells and TAMs secrete inflammatory factors, such as interleukin (IL)-2, IL-6 and CCL20, and that increased levels of circulating monocytic chemokines are observed in plasma samples from growing VS cases 45,46 . Supporting this, we have shown that classically-activated TAMs and transitioning monocytes have extensive interaction networks in Antoni A regions, namely with other myeloid cells, vasculature and some Schwann cell populations.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies highlight the crucial roles of macrophages in cancer therapy response and resistance, including chemotherapy, radiotherapy, and PDL1-based immunotherapy (Furuse et al, 2020;. Moreover, clinical trials of macrophage-targeted therapies have been started such as the engineered mononuclear phagocytes (Brempelis et al, 2020) and chimeric antigen receptor macrophages (CAR-M) (Klichinsky et al, 2020;, these therapeutic approaches stem from bench-top discoveries like recruitment and differentiation (Hannan et al, 2023), functional reprogramming (Willingham et al, 2012), and integration (Dang et al, 2021), highlighting the importance of basic research and preclinical study for the development of effective cancer treatment.…”
Section: Open Accessmentioning
confidence: 99%
“…Clinical studies highlight the crucial roles of macrophages in cancer therapy response and resistance, including chemotherapy, radiotherapy, and PDL1-based immunotherapy ( Furuse et al, 2020 ; Liu et al, 2020 ). Moreover, clinical trials of macrophage-targeted therapies have been started such as the engineered mononuclear phagocytes ( Brempelis et al, 2020 ) and chimeric antigen receptor macrophages (CAR-M) ( Klichinsky et al, 2020 ; Wang et al, 2022 ), these therapeutic approaches stem from bench-top discoveries like recruitment and differentiation ( Hannan et al, 2023 ), functional reprogramming ( Willingham et al, 2012 ), and integration ( Dang et al, 2021 ), highlighting the importance of basic research and preclinical study for the development of effective cancer treatment.…”
Section: Introductionmentioning
confidence: 99%